Exploration of Mathematical Literacy the Concept of Structural Geometry and Design in the Death Car Monument in Bondowoso - Fachrudi, Della Septania; panglipur, indah rahayu; Marsidi, Marsidi (Journal of Mathematics, Computations and Statistics, 2025)
This research aims to explore mathematical literacy through the structure and design of the Death Train Monument in Bondowoso as a medium for learning geometric concepts. With an exploratory approach and descriptive method, data were collected through observation and documentation to identify geometric elements such as trapezoids, rectangles, circles, cuboids, and geometric transformations. The research results show that the monument not only has historical value but also contains various geometric shapes that can be utilized as contextual learning resources in mathematics education based on local culture. This research recommends the integration of ethnomathematics in education as an effort to enhance mathematical literacy and appreciation for cultural heritage.